2017
DOI: 10.12965/jer.1735150.575
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vigorous physical activity on blood lipid and glucose

Abstract: The aim of the study is to investigate how the participation of vigorous physical activities in the health examination contributes to blood lipid and blood glucose. A total of 56,810 workers from the Ulsan University Hospital in Ulsan, Subjects were tested for health checkups from February to November in 2016. The subject is those who does not have medical history, current ailments, and medication histories, and selected those who conducted the study of subjects tested to research. And this study did not consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
(24 reference statements)
2
4
0
Order By: Relevance
“…These findings validate the previous data outside NAFLD and highlight the health benefits of vigorous PA for improved survival. 18,20,23,25,26 Additionally, our sensitivity analysis confirmed that it is the presence of vigorous activity where at least 50% of PA time is spent as vigorous had a protective effect.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…These findings validate the previous data outside NAFLD and highlight the health benefits of vigorous PA for improved survival. 18,20,23,25,26 Additionally, our sensitivity analysis confirmed that it is the presence of vigorous activity where at least 50% of PA time is spent as vigorous had a protective effect.…”
Section: Discussionsupporting
confidence: 65%
“…These benefits include improvement in lipid profiles, CVD risk factors, CVD mortality, improvement in mental health and all-cause mortality. [18][19][20][21][22][23][24][25][26][27] However, to our knowledge, the specific impact of vigorous PA among adults with NAFLD has not been measured, nor has specific guidance on activity intensity relative to total volume been proposed. Therefore, we investigated the association of the proportion of vigorous activity with all-cause mortality among adults with NAFLD using a nationally representative sample of the U.S. population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…High intensity training has been shown to increase glucose uptake during and post exercise 25 37 38. Engaging in vigorous physical activity also provides a better lipid profile that may help to prevent insulin resistance 39 40. Therefore, highly active individuals may have an advantage with higher insulin sensitivity and glucose metabolism during longer hours lying down to prevent or delay the onset of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity at various stages of life plays a valuable role, from ensuring mobility, enabling recreation and maintaining social interaction, to the possibility of maintaining everyday activity and independence at an elderly age. Regular exercise and PA normalise glycaemia and positively affect the lipid pro le [9], body composition, the functions of blood vessels, lung function, immune system and cardiac output [10]. On the contrary, I-Min Lee et al [11] indicated that physical inactivity (which was de ned as insu cient PA) causes 6-10% of several major non-communicable diseases, including coronary heart disease, type 2 diabetes, and breast and colon cancers.…”
Section: Introductionmentioning
confidence: 99%